2014
DOI: 10.2485/jhtb.23.239
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Bone Mineral Densities of Cervical and Lumbar Vertebrae in Postmenopausal Women

Abstract: For dental implant treatment, it is important to assess the general bone condition. Using multi-slice CT scans, we assessed the relationships between the bone mineral densities (BMDs) of the cervical and lumbar vertebrae in postmenopausal women to see if such data might be useful for imaging-based diagnosis prior to dental implant treatment. Thirty postmenopausal women were enrolled in this investigation, and their third cervical vertebrae were scanned for BMD using multi-slice computed tomography (CT) while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Correlation coefficients between BMDs of the lumbar vertebrae and values using quantitative ultrasound densitometry ranged from 0.433 to 0.640 10) . In previous studies, the BMD of the third cervical vertebra and MCI-MSCT were proposed to evaluate the influence of the general bone condition in imaging diagnosis for dental implant treatment using multi-slice CT 6,7) . Celenk and Celenk reported that the relationship between the age and CT values of the fifth cervical vertebra was negatively correlated (r = 0.354) in the total subjects, with 68 men and 46 women, using a linear equation (y=-2.06x+485.86) 11) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation coefficients between BMDs of the lumbar vertebrae and values using quantitative ultrasound densitometry ranged from 0.433 to 0.640 10) . In previous studies, the BMD of the third cervical vertebra and MCI-MSCT were proposed to evaluate the influence of the general bone condition in imaging diagnosis for dental implant treatment using multi-slice CT 6,7) . Celenk and Celenk reported that the relationship between the age and CT values of the fifth cervical vertebra was negatively correlated (r = 0.354) in the total subjects, with 68 men and 46 women, using a linear equation (y=-2.06x+485.86) 11) .…”
Section: Discussionmentioning
confidence: 99%
“…The super-cervical vertebrae have been included in scans of jaws using multi-slice CT, and a strong correlation between BMDs of the cervi cal and lu mbar vertebrae has been n oted i n postmenopausal women 6) . The BMD of the third cervical vertebra was proposed to evaluate the influence of the general bone condition.…”
Section: Introductionmentioning
confidence: 99%
“…CT analysis of the head and neck region was performed to investigate the area of the lesion and determine the extent of resection. Regions of interest with a 0.597 cm 2 area were set in the body of the third cervical vertebra, as previously described [ 24 ]. The CT values were averaged, and the mean CT value was transformed into the bone mineral density (BMD).…”
Section: Methodsmentioning
confidence: 99%
“…The data on BMDs of the lumbar vertebrae (L2, 3, and 4) measured using DXA (Norland XR36, Fisher BioMedical Inc., Venice, FL) and reported in our previous study 11) were used. The mean period between multislice CT scans and DXA for the lumbar vertebrae was 0.7 years (s.d.…”
Section: Measurement Of Bmds Of the Lumbar Vertebraementioning
confidence: 99%
“…[8][9][10] The super-cervical vertebrae were included in scans of jaws, and a strong correlation between BMDs of the third cervical and lumbar vertebrae was noted in postmenopausal women. 11) On the other hand, measurement of the mandibOkajimas Folia Anat. Jpn., 91(3): 49-55, November, 2014…”
Section: Introductionmentioning
confidence: 99%